Isolation and Biological Characterization of Newcastle Disease Virus (NDV) Field Isolate Pigeon (Columba livia) from Live Bird Market, East Java in 2019 - Venri Novryantoro; Fedik Abdul Rantam; Suwarno Suwarno; Rahaju Ernawati; Jola Rahmahani (Universitas Airlangga, 2023)
Background: Avian Paramyxovirus (APMV) type-1 is the leading cause of Newcastle Disease (ND) and taxonomically belongs to the family Paramyxoviridae, genus Avulavirus. Due to its high transmission rate, Newcastle Disease (ND) is included in the A list by the OIE. Purpose: To determine the biological characterize the Newcastle Disease Virus (NDV) field isolate of pigeons (Columba livia) using Mean Death Time (MDT), Intracerebral Pathogenicity Index (ICPI), and Intravenous Pathogenicity Index (IVPI). Methods: Twenty pigeon organ samples were obtained from bird markets in East Java, and one was used as a positive control (LaSota). Organs were isolated from embryonated chicken eggs, identified by the HA test, and then confirmed by the HI test. Furthermore, positive samples were tested for MDT with a 10-1-10-18 dilution (0.1 ml and observed for eight days. The ICPI test used a fresh NDV suspension (0.05 ml and was observed for eight days. The IVPI test used a dose of 0.1 ml and was observed for ten days. Result: The MDT values of isolates MB1/NDV/19, MB2/NDV/19, MB3/NDV/19, and MG1/NDV/19 were 91.2 hours, 112.8 hours, 110.4 hours, and 124,8 hours. The ICPI values of isolate MB1/NDV/19 was 0.2375, MB2/NDV/19 was 0.375, MB3/NDV/19 was 0.5375, and MG1/NDV/19 was 0.3. The IVPI value of isolate MB1/NDV/19 was 0, MB2/NDV/19 was 0, MB3/NDV/19 was 0, and MG1/NDV/19 was 0. Conclusion: All four field samples were positive for NDV as a lentogenic strain based on the MDT, ICPI, and IVPI tests.